2015
DOI: 10.1007/s10549-015-3280-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of physical examination, ultrasound, and ultrasound combined with fine-needle aspiration for axilla staging of primary breast cancer

Abstract: The aim of this study was to compare the efficacy of physical examination (PE), ultrasound (US), and US combined with fine-needle cytology (US-FNAC) in evaluation of node status before sentinel lymph node biopsy (SLNB) for breast cancer patients. We performed a retrospective study of 3,781 breast cancer patients and calculated the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy for PE, US, and US-FNAC, respectively. A total of 3,175 cases were documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 26 publications
1
33
2
Order By: Relevance
“…We established a new US criterion (dividing patients into potential malignancy and follow‐up groups) to evaluate the recurrent and nonrecurrent level II and III axillary lymph nodes in this study. Based on this criterion, the sensitivity, specificity, accuracy, positive predictive value, negative predictive value, false‐positive rate, false‐negative rate, and area under the receiver operating characteristic curve of axillary US were higher than those reported in previous studies . Another reason for the difference might be that the previous studies did not divide the axillary lymph nodes into various levels, whereas this study differentiated between the US findings for level I and level II and III lymph nodes.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…We established a new US criterion (dividing patients into potential malignancy and follow‐up groups) to evaluate the recurrent and nonrecurrent level II and III axillary lymph nodes in this study. Based on this criterion, the sensitivity, specificity, accuracy, positive predictive value, negative predictive value, false‐positive rate, false‐negative rate, and area under the receiver operating characteristic curve of axillary US were higher than those reported in previous studies . Another reason for the difference might be that the previous studies did not divide the axillary lymph nodes into various levels, whereas this study differentiated between the US findings for level I and level II and III lymph nodes.…”
Section: Discussioncontrasting
confidence: 58%
“…Based on this criterion, the sensitivity, specificity, accuracy, positive predictive value, negative predictive value, false-positive rate, false-negative rate, and area under the receiver operating characteristic curve of axillary US were higher than those reported in previous studies. 4,[14][15][16] Another reason for the difference might be that the previous studies 4, [14][15][16] did not divide the axillary lymph nodes into various levels, whereas this study differentiated between the US findings for level I and level II and III lymph nodes. Moreover, ALND was performed in all cases in our study, which was different from the studies by Snider et al 8 and Susini et al, 6 in which sentinel lymph node dissection was used.…”
Section: Discussionmentioning
confidence: 68%
“…The sensitivity and specificity of PE have been shown to be 30% and 93% in one study, and others have demonstrated a false‐positive rate of 53% . The use of AUS with PE has been shown to improve the accuracy of pretreatment nodal evaluation, with the sensitivity and specificity being 59% and 89%, respectively . In the present study, AUS identified abnormal appearing LNs in 63% (76/120) of patients with a negative PE, of which 70% (53/76) were biopsy‐proven positive.…”
Section: Discussionsupporting
confidence: 52%
“…11 The use of AUS with PE has been shown to improve the accuracy of pretreatment nodal evaluation, with the sensitivity and specificity being 59% and 89%, respectively. 12,13 In the present study, AUS identified Characteristics of metastatic appearing LNs on AUS include cortical thickening, rounding of node with loss of fatty hilum and loss of normal architecture and have been shown to have a high correlation with metastatic disease on final pathology. 16,17 However, a multicenter study showed that 29% of patients with normal appearing LNs by AUS or with negative biopsy results still had positive LNs on final pathology.…”
Section: Re Sultsmentioning
confidence: 67%
“…2 They performed a retrospective study of 3,781 breast cancer patients and calculated the sensitivity, specificity, PPV, NPV, and accuracy for PE, US, and US-FNAC, respectively. Abnormal axillary nodes under US were detected in 1,152 cases, among which 821 were proven to have positive nodes by FNAC.…”
Section: Discussionmentioning
confidence: 99%